006.072 GENERAL GUIDELINES FOR QUALITY MANAGEMENT AND TECHNOLOGIES IN THE METALLURGICAL INDUSTRY SUPPLY CHAIN. - Mamadalieva, dildora (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, a model supporting the quality management and technological processes of the supply chain in the metallurgical industry has been developed. This model is general and universal in nature, and the recommended guidelines can be implemented in various manufacturing companies. The assumptions of this model were developed on the basis of observations of Mexmash enterprise, one of the largest metallurgical plants in our region. This developed model leads to a significant improvement in the activities of metallurgical industry enterprises in terms of building effective forms of communication with customers, implementing logistics processes based on customer requirements, and providing high-level customer service. The supply chain aims to minimize inventory levels and raw material costs while maintaining the highest quality standards. The production logistics activity of the subsystem is aimed at increasing the efficiency of production processes, at the same time increasing quality standards and reducing the number of inconsistencies. In turn, the distribution subsystem integrates logistics processes, marketing, and quality to improve overall customer service.